2011
DOI: 10.1080/01639269.2011.592803
|View full text |Cite
|
Sign up to set email alerts
|

Social Gerontology—Integrative and Territorial Aspects: A Citation Analysis of Subject Scatter and Database Coverage

Abstract: To determine the mix of resources used in social gerontology research, a citation analysis was conducted. A representative sample of citations was selected from three prominent gerontology journals and information was added to determine subject scatter and database coverage for the cited materials. Results indicate that a significant portion of gerontology research, even from a social science perspective, relies roughly equally on medical resources as it does social science resources. Furthermore, there is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Evidence indicates that the ability of citation searching as a supplementary search technique to find additional unique records in a systematic literature search varies between reviews 6. Searches for particular study designs (qualitative, mixed method, observational, prognostic, or diagnostic test studies) or health science topics such as non-pharmacological, non-clinical, public health, policy making, service delivery, or alternative medicine have been linked with effective supplementary citation searching 19202122. The underlying reasons include poor transferability to text based searching owing to poor conceptual clarity, inconsistent terminology, or vocabulary overlaps with unrelated topics 5.…”
Section: Tarcis Statement: Final Recommendations Rationale and Explan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that the ability of citation searching as a supplementary search technique to find additional unique records in a systematic literature search varies between reviews 6. Searches for particular study designs (qualitative, mixed method, observational, prognostic, or diagnostic test studies) or health science topics such as non-pharmacological, non-clinical, public health, policy making, service delivery, or alternative medicine have been linked with effective supplementary citation searching 19202122. The underlying reasons include poor transferability to text based searching owing to poor conceptual clarity, inconsistent terminology, or vocabulary overlaps with unrelated topics 5.…”
Section: Tarcis Statement: Final Recommendations Rationale and Explan...mentioning
confidence: 99%
“…6 Searches for particular study designs (qualitative, mixed method, observational, prognostic, or diagnostic test studies) or health science topics such as non-pharmacological, non-clinical, public health, policy making, service delivery, or alternative medicine have been linked with effective supplementary citation searching. [19][20][21][22] The underlying reasons include poor transferability to text based searching owing to poor conceptual clarity, inconsistent terminology, or vocabulary overlaps with unrelated topics. 5 The ability of citation searching to find any publication type including unpublished or grey literature or literature that is not indexed in major databases (eg, concerning a developing country) might also be relevant.…”
Section: Rationale and Explanation Supporting Recommendationmentioning
confidence: 99%
“…just the year) in Scopus or, in one case, the reference was omitted in Scopus. Incomplete bibliographic information in Scopus for cited items that are not journal articles has been reported before (Bergman, 2011).…”
Section: Procedures For Citation Analysismentioning
confidence: 99%
“…20 Stating that social gerontology "clearly fits the paradigm of an interdisciplinary field," Elaine Lasda Bergman found that 23.7 percent of the journal articles cited were in the social gerontology field, concluding that "there is a small, definitive core of materials specific to gerontological research." 21 Literature use by scholars in anthropology, as reported by William Robinson and Paul Posten, showed that 27 percent of journal citations were classified in anthropology using the LCC class GN. 22 As described by Thomas Weissinger in 2010, citations in two core black studies journals cited other black studies journals at a rate of 23 percent, demonstrating that the field has a high level of interdisciplinarity.…”
Section: Literature Reviewmentioning
confidence: 99%